Studies of lightning overvoltages of 115 kV CMU GIS substation - Thanasaksiri T. (2017)
This paper presents the analysis of lightning overvoltage for the new coming 115 kV CMU (ChiangMai University) GIS (Gas Insulated Switchgear) substation applying simplified models. The GIS being considered here is connected to an overhead line through XLPE underground cables. The sensitivity analysis of lightning overvoltage have been evaluated using ATP-EMTP. Factors including, pole footing resistance, cable length and additional surge arrester installed which gives the variation of overvoltages in GIS have also been considered. Finally, means to reduce the lightning overvoltages for the new coming 115 kV CMU GIS substation will be recommended. © 2012 IEEE.